The optical transient search in the Bamberg Southern sky survey: Preliminary results - Hudec, R.; Kopel, F.; Krapp, P.; Heber, Ulrich; Cayé, W. (Acta Polytechnica, 2012)
A large fraction of gamma-ray bursts temporarily emit optical light, i.e. optical afterglows and optical transients. So far, optical transients have only been detected after related gamma-ray satellite detection. However, taking into account their optical magnitudes at maximum light, these objects should be detectable in various historical and recent optical surveys, including the photographic sky patrol. Here we report on an extended study based on blink-comparison of 5004 Bamberg Observatory Southern Sky Patrol Plates performed within a student high school project (Jugend Forscht).
CRIS-Team Scopus Importer:2020-12-21
Keywords: Bursts-optical; Gamma-ray; Sky plate archives; Surveys-photographic; Transients-sky